2020
DOI: 10.1177/1078155220984239
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity pneumonitis related to imatinib mesylate therapy in a patient with chronic myeloid leukemia

Abstract: Introduction Pulmonary toxicity causally related to Imatinib (IM) therapy is uncommon in patients with chronic myeloid leukemia. Case report A 61-year-old patient with chronic myeloid leukemia was treated with IM at 400 mg daily dose. One month within IM, he developed skin lesions and then acute dyspnea and non-productive cough. Chest radiograph and high-resolution lung computed tomography (CT) revealed bilateral reticulonodular infiltration in both lungs. According to Naranjo's algorithm, the causality relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Imatinib is in general well tolerated by patients and adverse events can be divided into hematological (anemia, neutropenia, thrombocytopenia) vs nonhematological (cardiovascular, pancreatic, hepatic, cutaneous, gastrointestinal effects; fluid retention, bleeding, musculoskeletal disorders, neuropathy, ocular toxicity, infectious, or metabolic events). Cases with pneumonitis and pulmonary interstitial fibrosis like in the case here described have been reported previously 3–5 but rarely outside Asia 6,7 . Several authors have reported on succesful outcome of pulmonary adverse events upon discontinuation of imatinib in combination with initiation of corticosteroid treatment 3–7 .…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Imatinib is in general well tolerated by patients and adverse events can be divided into hematological (anemia, neutropenia, thrombocytopenia) vs nonhematological (cardiovascular, pancreatic, hepatic, cutaneous, gastrointestinal effects; fluid retention, bleeding, musculoskeletal disorders, neuropathy, ocular toxicity, infectious, or metabolic events). Cases with pneumonitis and pulmonary interstitial fibrosis like in the case here described have been reported previously 3–5 but rarely outside Asia 6,7 . Several authors have reported on succesful outcome of pulmonary adverse events upon discontinuation of imatinib in combination with initiation of corticosteroid treatment 3–7 .…”
Section: Discussionsupporting
confidence: 57%
“…Cases with pneumonitis and pulmonary interstitial fibrosis like in the case here described have been reported previously [3][4][5] but rarely outside Asia. 6,7 Several authors have reported on succesful outcome of pulmonary adverse events upon discontinuation of imatinib in combination with initiation of corticosteroid treatment. [3][4][5][6][7] Ohnishi et al however reported on 27 patients with Imatinib-induced interstitial lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations